Efficient Removal of Methylene Blue Dye and Ofloxacin Antibiotic using Eggshell Waste as Adsorbent - Chunkaew, Sarapee; Ruang-On, Somporn; Nuengmatcha, Prawit (Asian Journal of Chemistry, 2026)
Eggshell waste, an inexpensive and abundant material, serves as an eco-friendly adsorbent for wastewater treatment. This study evaluates its efficiency in removing methylene blue (MB) dye and ofloxacin (OFX) antibiotic from aqueous solutions. The adsorbent was characterized by Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) to assess its surface morphology and composition. Batch adsorption experiments identified the optimal conditions as 0.04 g of adsorbent, a contact time of 120 min, an initial MB concentration of 4 mg/L and an initial OFX concentration of 6 mg/L. Under these conditions, the removal efficiencies reached 73.01% for MB and 85.34% for OFX, with maximum adsorption capacities of 9.95 mg/g and 0.93 mg/g, respectively. Methylene blue (MB) dye adsorption was strongly affected by solution pH and electrostatic interactions, whereas OFX adsorption involved electrostatic attraction, hydrogen bonding and surface complexation. Kinetic studies revealed that MB adsorption followed a multi-step diffusion mechanism, while OFX adsorption was best described by the pseudo-second-order kinetic model. Thermodynamic analysis indicated that the adsorption of both pollutants was spontaneous and endothermic, accompanied by positive entropy changes. The adsorbent exhibited good regeneration performance, retaining more than 50% of its MB and OFX removal efficiencies after five adsorption-desorption cycles. These findings demonstrate that the eggshell waste calcined at 600 ºC is an efficient, reusable and sustainable adsorbent with considerable potential for the treatment of dye- and antibiotic contaminated wastewater.